2018
DOI: 10.1007/s41781-018-0005-0
|View full text |Cite|
|
Sign up to set email alerts
|

The Archive Solution for Distributed Workflow Management Agents of the CMS Experiment at LHC

Abstract: The CMS experiment at the CERN LHC developed the Workflow Management Archive system to persistently store unstructured framework job report documents produced by distributed workflow management agents. In this paper we present its architecture, implementation, deployment, and integration with the CMS and CERN computing infrastructures, such as central HDFS and Hadoop Spark cluster. The system leverages modern technologies such as a document oriented database and the Hadoop eco-system to provide the necessary f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We found that the Spark platform significantly improved our analytics capabilities. For instance, in the WMArchive [12] system we can promptly perform the following tasks:…”
Section: Cms Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the Spark platform significantly improved our analytics capabilities. For instance, in the WMArchive [12] system we can promptly perform the following tasks:…”
Section: Cms Monitoringmentioning
confidence: 99%
“…log files are usually streamed to HDFS in native data-format (JSON), the database tables are easily converted into CSV data-format, while large unstructured data sets, e.g. in case of the WMArchive system [12], are converted into compact, fast, binary Avro dataformat with a pre-defined schema. Fortunately, the HDFS libraries support a broad variety of HTCondor logs [8] JSON 11.1 TB AAA (Global Data Access) logs [9] JSON 11 TB EOS logs [10] JSON 5.3 TB FTS (File Transfer System) logs [11] JSON 4.2 TB PhEDEx snapshots [4] CSV 3.3 TB WMArchive logs [12] Avro 1.3 TB CMSSW (CMS SoftWare framework) logs Avro 0.5 TB DBS tables [4] CSV 0.3 TB JobMonitoring logs Avro 0.2 TB data-formats, and the Spark framework is guaranteed to work seamlessly and efficiently with all of them.…”
Section: Current Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Several models to predict the operator's action based on this input have been studied in the last years [2]. Additionally, for each thrown error code a snippet of the error log that contains the occurred exception is stored by the CMS WMArchive service [3]. The WMArchive entries are analyzed with Apache Spark on the CERN SWAN platform for interactive computing [5].…”
Section: Introductionmentioning
confidence: 99%